Konstitucinis teisėjo ir teismų nepriklausomumo principas: tarp konstitucinio imperatyvo ir gyvenimo realybės - Jočienė, Danutė (Vilnius University Open Series, 2024)
The independence of the judiciary as a fundamental constitutional imperative has expressis verbis been enshrined in Paragraph 2 of Article 109 of the Constitution of the Republic of Lithuania adopted in the Referendum of 25 October 1992. In the presently mentioned Article, it is emphasized that “When administering justice, judges and courts shall be independent.” The Constitutional Court has held more than once that the independence of judges and courts is one of the essential principles of a democratic State under the rule of Law: while administering justice, courts must ensure the implementation of the right embodied in the Constitution, laws and other legal acts, guarantee the supremacy of Law, and protect human rights and freedoms. Already in the Ruling of 6 December 1995, the Constitutional Court held that one of the fundamental distinguishing characteristics of a democratic State is the principle of the independence of the judiciary. All democratic States adhere to this principle, and, as the historical facts illustrate, the denial of this principle is an immanent feature of totalitarian and authoritarian regimes. The independence of judges and courts is not an end in itself: this is a necessary condition of the protection of the human rights and freedoms, not a privilege but one of the main duties of a judge and courts arising from the right of every person who believes that his rights or freedoms have been violated to an independent and impartial arbiter of the dispute, which, under the Constitution and laws, would in essence solve the dispute at law, guaranteed in the Constitution (inter alia, in Paragraph 2 of Article 109, as well as in Paragraph 1 of Article 30, in which it is prescribed that the person whose constitutional rights or freedoms are violated shall have the right to apply to court) (see, among many others, the Constitutional Court’s rulings of 6 December 1995, 1 October 1997, 8 May 2000, 4 March 2003, 17 August 2004, 29 December 2004, 28 March 2006, 9 May 2006).